2021
DOI: 10.3389/fmars.2021.715846
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and Sexual Maturity of European Sardine (Sardina pilchardus) in the Central Mediterranean Sea

Abstract: Understanding drivers of fish maturity is essential to predict the productivity, stability, and resiliency of exploited populations. Size at maturity for European sardine (Sardina pilchardus) in the Central Mediterranean Sea has never been published within rigorous peer review process. In the past, stock assessment working groups in the Mediterranean requested such information; however, the size at which 50% of the fish population reaches the sexual maturity (L50) often received weak estimates based on a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…Moreover, significant differences between the sexes in GSI were identified only for active spawners (Figure 3A), with larger values observed in females. Our results are similar to those of Basilone et al [12] for a study in the Central Mediterranean, although they differed from other studies in which males were identified as the individuals with the highest values of GSI [13]. According to Ganias et al [2], isometric ovarian growth has been shown for all the developmental stages in sardines except for hydration, and so the relative weight of the ovaries (i.e., the gonadosomatic index, GSI) remains stable with body size, except in this phase (i.e., corresponding to hydration and ovulation in females [48]).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, significant differences between the sexes in GSI were identified only for active spawners (Figure 3A), with larger values observed in females. Our results are similar to those of Basilone et al [12] for a study in the Central Mediterranean, although they differed from other studies in which males were identified as the individuals with the highest values of GSI [13]. According to Ganias et al [2], isometric ovarian growth has been shown for all the developmental stages in sardines except for hydration, and so the relative weight of the ovaries (i.e., the gonadosomatic index, GSI) remains stable with body size, except in this phase (i.e., corresponding to hydration and ovulation in females [48]).…”
Section: Discussionsupporting
confidence: 93%
“…The reproductive potential of the small pelagic European sardine (Sardina pilchardus (Walbaum, 1792)) depends on its spawning frequency and batch fecundity [8], as it is a multiple spawner species with an indeterminate annual fecundity that serially releases batches of pelagic eggs at intervals (i.e., batch spawner) within the spawning season [9,10]. Its spawning season occurs during the winter [2,11] along its distributional range, although monthly differences exist associated with sardine stock genetic features and environmental characteristics of the area [12]. Production of such a great number of eggs during an extended period requires a considerable amount of energy resources that can be obtained (1) from energy reserves accumulated prior to spawning, (2) directly from food input during the spawning season, or (3) from both sources [13] so that the population's reproductive potential can be influenced by the condition of the fish, which has a direct impact on their recruitment strength [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size range among locations was restricted to the most similar to cover an identical age range and strict as possible to avoid multiple classes. Sample locations concerning Mediterranean waters had smaller sizes, related to the lower average adult individual size (Albo‐Puigserver et al ., 2021; Basilone et al ., 2021; Van Beveren et al ., 2016). Sample collection was opportunistic and primarily dependent on small pelagic trawls during research surveys.…”
Section: Methodsmentioning
confidence: 99%
“…The peak of reproductive activity occurs between November and February, primarily depending on environmental parameters such as temperature (Zorica et al, 2019). In contrast to the AS, the spawning period for S. pilchardus appears to end earlier in other Mediterranean areas (Tsikliras et al, 2010;Basilone et al, 2021). The Adriatic anchovy spawns from the end of March (winter) to October (autumn), with its peak spawning season occurring in July (Zorica et al, 2020).…”
Section: Ichthyo-biodiversity In the Asmentioning
confidence: 99%